2020
DOI: 10.1097/bot.0000000000001787
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Skin Suture Pattern on Incision Perfusion Using Intraoperative Laser Angiography: A Randomized Clinical Trial of Patients With Ankle Fractures

Abstract: Objectives: To assess which skin suture pattern—simple, vertical mattress, horizontal mattress, Allgöwer–Donati (AD), or running subcuticular—enables the greatest degree of perfusion as measured by indocyanine green laser angiography after ankle fracture surgery. Design: Prospective, randomized. Setting: Level 1 Academic Trauma Center. Patients/Participants: Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…RSC resulted in the most robust perfusion, VM closure resulted in intermediate perfusion, and staple closure yielded the poorest perfusion. Shorten et al 16 reported similar results in a RCT of patients undergoing ankle fracture ORIF with RSC resulting in superior perfusion compared with simple, horizontal mattress, VM, and Allgöwer-Donati techniques. These studies were motivated by previous studies that had demonstrated perfusion to be one of the most physiologically important factors in wound healing with increased oxygen tension resulting in increased deposition of collagen.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…RSC resulted in the most robust perfusion, VM closure resulted in intermediate perfusion, and staple closure yielded the poorest perfusion. Shorten et al 16 reported similar results in a RCT of patients undergoing ankle fracture ORIF with RSC resulting in superior perfusion compared with simple, horizontal mattress, VM, and Allgöwer-Donati techniques. These studies were motivated by previous studies that had demonstrated perfusion to be one of the most physiologically important factors in wound healing with increased oxygen tension resulting in increased deposition of collagen.…”
Section: Discussionmentioning
confidence: 80%
“…26 Although RSC has been shown to have superior wound perfusion and cosmesis across multiple surgical subspecialties, its effect on postoperative wound complications in orthopaedic surgery is scarce and conflicting. [13][14][15][16][17][18][19][20][21] A meta-analysis of 6 studies by Smith et al 4 found that the risk of postoperative wound complications was 3.8 times greater for patients who received staples compared with those who received sutures. A subsequent systematic review and meta-analysis of 12 studies by Krishnan et al 5 found no differences in the rate of wound complications between these groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Allgöwer-Donati suture technique has been used for ankle wound closure and maintains control of skin tension in orthopaedic surgery 9 . This technique achieves some cosmetic results by means of unilateral intermittent embedding of the wound.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, various methods have been studied analytically and experimentally to evaluate the mechanical properties of different suture patterns. For example, the strength of various suture patterns used for incision closure was characterized through tensile tests, the performance of conventional and new suture techniques used for the closure of the linea alba was evaluated clinically through wound examination and ultrasonic probing, and the impact of the skin suture pattern on incision perfusion was assessed by indocyanine green laser angiography imaging . However, detecting tensile stress through the measurement of localized strain in sutured skins remains challenging because of the unique and complex properties of each sutured skin specimen and the lack of compliant sensors capable of monitoring large levels of strain in vivo .…”
mentioning
confidence: 99%